Circulating tumor cells and DNA as liquid biopsies - Heitzer, Ellen (BioMed Central, 2013)
For cancer patients, the current approach to prognosis relies on clinicopathological staging, but usually this provides little information about the individual response to treatment. Therefore, there is a tremendous need for protein and genetic biomarkers with predictive and prognostic information. As biomarkers are identified, the serial monitoring of tumor genotypes, which are instable and prone to changes under selection pressure, is becoming increasingly possible. To this end, circulating tumor cells (CTCs) or circulating tumor DNA (ctDNA) shed from primary and metastatic cancers may allow the non-invasive analysis of the evolution of tumor genomes during treatment and disease progression through 'liquid biopsies'. Here we review recent progress in the identification of CTCs among thousands of other cells in the blood and new high-resolution approaches, including recent microfluidic platforms, for dissecting the genomes of CTCs and obtaining functional data. We also discuss new ctDNA-based approaches, which may become a powerful alternative to CTC analysis. Together, these approaches provide novel biological insights into the process of metastasis and may elucidate signaling pathways involved in cell invasiveness and metastatic competence. In medicine these liquid biopsies may emerge to be powerful predictive and prognostic biomarkers and could therefore be instrumental for areas such as precision or personalized medicine.